System Dynamics Modelling of Remanufacturing and Recycling Mode Based on Closed-Loop Across-Chain Competition - Shidi Miao; Deyun Chen; Tengfei Wang (Discrete Dynamics in Nature and Society)
To face the reality of resources exhaustion, the significance of recycling and remanufacturing in the closed-loop chain has become quite evident. This paper constructs a competitive recycling and remanufacturing model of the closed-loop supply chain through a case study of Midea Corp. and Gree Corp. and explores the impact of two recycling modes on total revenue of the supply chain and market share. The simulation results show that the total revenue of the supply chain will benefit from the increasing coverage points by the third party and the increasing environmental awareness of certain regions. The retailers show more enthusiasm of recycling through certain amendment of the contract between manufacturers and retailers. The time of payment could be shortened in closed loop. Moreover, the improvement of recycling mechanism of the retailers can enlarge the share of supply chain market. Guiding role of the proposed model and the simulation results played in establishing a better supply chain mode is presented.